Egy észszerű nyugdíjreform csomag: Magyarország, 2025 - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
– Due to an EU directive, with tight deadlines, the Hungarian government has to work out program, including a pension reform. The plan is to be discussed publicly and made into a law. The last public and detailed pension package was a Working Paper of the National Bank of Hungary, 2016, which needs updating. Before the government publishes a new program, I have found it worthwhile to outline a rational pension reform package, which would make the current system more efficient and fairer. First, I outline the current system, then I present the simpler and the more complicated reforms. Here I only mention the first simple step: to return to the practice of Budgetary Council between 2008 and 2010, where the Secretariate had dozens of independent experts working on issues similar to the current pension package. I do not deal with the political conditions of achieving such a reform.
Keywords: H55; 330; pension reforms; Hungary; EU initiatives